Synaptic Plasticity, a Prominent Contributor to the Anxiety in Fragile X Syndrome - Tao Yang; Huan Zhao; Changbo Lu; Xiaoyu Li; Yingli Xie; Hao Fu; Hui Xu (Neural Plasticity)
Fragile X syndrome (FXS) is an inheritable neuropsychological disease caused by expansion of the CGG trinucleotide repeat affecting the fmr1 gene on X chromosome, resulting in silence of the fmr1 gene and failed expression of FMRP. Patients with FXS suffer from cognitive impairment, sensory integration deficits, learning disability, anxiety, autistic traits, and so forth. Specifically, the morbidity of anxiety in FXS individuals remains high from childhood to adulthood. By and large, it is common that the change of brain plasticity plays a key role in the progression of disease. But for now, most studies excessively emphasized the one-sided factor on the change of synaptic plasticity participating in the generation of anxiety during the development of FXS. Here we proposed an integrated concept to acquire better recognition about the details of this process.